2011
DOI: 10.1002/cncr.26065
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary metastases in patients with recurrent, treatment‐resistant meningioma

Abstract: BACKGROUND:Meningioma is the most common extra-axial primary intracranial tumor in adults that rarely metastasizes outside of the central nervous system (CNS). Among recognized sites of metastases, the lung is the most common, but the importance of lung metastases relative to prognosis is unknown. 111 Indium ( 111 In)-octreotide scintigraphy (octreotide scanning) is a valuable imaging modality with which to evaluate intracranial meningiomas and their response to treatment with somatostatin analogues and has th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…Although metastasis of meningioma is a rare phenomenon in adult patients, it has been well-documented and its incidence has been estimated to be 0.1% (10,11). According to the results of the systematic review by Surov et al (12), metastatic lesions were localized most frequently in the lungs (37.2%), bones (16.5%), intraspinally (15.2%) and in the liver (9.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Although metastasis of meningioma is a rare phenomenon in adult patients, it has been well-documented and its incidence has been estimated to be 0.1% (10,11). According to the results of the systematic review by Surov et al (12), metastatic lesions were localized most frequently in the lungs (37.2%), bones (16.5%), intraspinally (15.2%) and in the liver (9.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Following gross total resection (GTR), meningiomas have a recurrence rate of 10% to 30% at 10 years, whereas tumors with subtotal resection (STR) have a 10-year recurrence rate of 61%. [28][29][30][31][32] Moreover, all tumor grades have been correlated with increased survival when treated with total resection as compared with STR. [33][34][35][36] In a multi-institutional retrospective study of 199 patients with high grade meningiomas, analysis of grade II meningiomas showed that patients younger than 60 years of age who had undergone Simpson grade 1 resections had longer overall survival.…”
Section: Prognostic Factorsmentioning
confidence: 97%
“…Initially used for scintigraphic imaging of NETs [26], Octreoscan is considered the gold standard for imaging gastroenteropancreatic (GEP) tumors and is more reliable and sensitive than magnetic resonance imaging (MRI) and computed tomography (CT) for diagnosis and staging. Recent studies have also demonstrated the use of this agent for the diagnosis of thymic tumors [27] and possibly in the assessment of pulmonary metastases in patients with recurrent, treatment-resistant meningioma [28].…”
Section: Detection Of Sstr Expression By Single-photon Emission Compumentioning
confidence: 98%